A criminalidade tomou conta da cidade: o cinturão de insegurança em Fortaleza, Ceará - Mendonça Neto, Aguimar (2024)
This paper investigates crime in the city of Fortaleza, capital of Ceará, using data from police reports to perform a cluster analysis, which identified the existence of a kind of belt of insecurity in the city. The insecurity belt is formed by neighborhoods with high crime rates, such as homicides, robberies and thefts. The neighborhoods that make up the belt are located in peripheral regions of the city, with low income and precarious infrastructure. Additionally, Principal Component Analyzes (PCA) were performed in order to reduce the dimensionality of the data. This identified that the main factors that are related to crime in Fortaleza are poverty, social inequality and low education. Crime in Fortaleza is a complex problem that requires integrated public policies to solve it. These policies must address the socio-economic factors that contribute to crime, such as poverty, social inequality and lack of opportunities. Finally, public policies are suggested to reduce crime, which should address the socioeconomic factors related to it.